Authoritarianism and Attitudes Toward Welfare Recipients Under Covid-19 Shock - Blanchet, Alexandre; Landry, Normand (Frontiers in Political Science, 2021)
This paper has looked at the evolution of attitudes towards welfare recipients and the impact of authoritarian dispositions on these attitudes in the context of the Covid-19 health crisis. We used two representative surveys, the first (n = 2054) conducted in the summer of 2019 and the second (n = 2060) in Quebec in June 2020, near the end of the first wave of the Covid-19 pandemic in the province. 1178 participants in the second survey had also participated in the first, allowing to analyze potential movement among many of the same individuals. Overall, while our results clearly indicated that authoritarian dispositions were associated with more negative views of welfare recipients, the pandemic does not appear to have affected the relationship between these attitudes and authoritarian traits. Additionally, we found no evidence that a direct measure of perceived threat moderated the relation between authoritarianism and attitude towards welfare recipients. Yet, we did find that, in the context of the pandemic, authoritarianism was associated with the attribution of lower deservingness scores to welfare recipients who were fit for work, suggesting that authoritarianism interacts with an important deservingness heuristic when evaluating who deserves to be helped.